I Guds Namn. Migration och främlingskap i Lennart Hager fors Längta hem. Om ett missionärsbarn i Kongo - Rinderle, Hanna (Folia Scandinavica Posnaniensia, 2019)
In this article I analyze the autobiographical novel Längta hem. Om ett missionärsbarn i Kongo (2003) by Lennart Hagerfors in order to understand how otherness is presented and how it is linked to the status of migration and being Swedish. I argue that the novel shows two distinct forms of otherness. The first is on the personal and individual level of the protagonist that is caused by his migration from Sweden to Congo. The other is on a cultural and national level, which situates Sweden in between the Congolese and French culture. While the first personal form of strangeness is viewed as problematic and must be overcome, the second form can be read as an expression of the positive Swedish self-image that situates Sweden outside of Europe’s colonial history and therefore posits Sweden as a type of humanitarian Great Power or global conscience.